Prospects for 3D-printing of clear aligners—a narrative review - Niu, Chenyang; Li, Dongwen; Zhang, Yujia; Wang, Yunkai; Ning, Shangbo; Zhao, Gang; Ye, Zhihui; Kong, Yu; Yang, Donghong (Frontiers in Materials, 2024)
Clear aligner therapy is a rapidly developing orthodontic treatment. 3D-printing technology, which enables the creation of complex geometric structures with high precision, has been used in dentistry. This article aims to summarize the various aspects of 3D-printing clear aligners and give an outlook on their future development. The traditional thermoforming technology is introduced and the principle and application of 3D-printed clear aligners and materials are introduced, as well as the application prospects of 3D-printed clear aligners. According to PRISMA statement, the relevant literature of 3D-printing clear aligner was searched in PubMed, Web of Science, Embase and other databases. We searched the related words in the MESH database and then carried out advanced searches. We read systematic review and conference papers to find the articles related to the subject and manually added and excluded articles by reading the title and abstract. The production of clear aligners combines computer-aided 3D analysis, personalized design and digital molding technology. The thickness and edges of the 3D-printed clear aligner can be digitally controlled, which allows appliance more efficiently fitted. Presently, the array of clear resins suitable for 3D-printing include photo polymeric clear methacrylate-based resin (Dental LT) (Form Labs, Somerville, Mass), aliphatic vinyl ester-polyurethane polymer (Tera Harz TC-85) (Graphy, Seoul, South Korea). They all have good biocompatibility. But no such material is currently approved on the market. Developing biocompatible resins and further improving the material's mechanical properties will be critical for the combination of 3D-printing and clear aligners. However, the literature on 3D-printed clear aligners is limited and lacks clinical application. Further in vivo and in vitro tests, as well as additional exploration in conjunction with corresponding cytological tests, are required for the research on available materials and machinery for 3D-printing clear aligners.